Respostas

2013-08-14T15:20:06-03:00
5x² - 11x + 6= 0

Δ = b² - 4ac
Δ =  (-11)² - 4.5.6
Δ =  121 - 120
Δ = 1

x = - 11 +- √ 1
            2.5
x = -11 +- 1
          10
x' = -11 + 1 = -10    = -1
         10         10

x'' = -11 - 1 = -12  = -1,2
         10         10

Solução = 1 e 1,2

Espero ter ajudado!
2 4 2
Muito obrigada, ajudou muito
Por nada! =D
2013-08-14T16:43:03-03:00
5x² - 11x + 6= 0

Δ = b² - 4ac
Δ =  (-11)² - 4.5.6
Δ =  121 - 120
Δ = 1

x = - 11 +- √ 1
            2.5
x = -11 +- 1
          10
x' = -11 + 1 = -10    = -1
         10         10

x'' = -11 - 1 = -12  = -1,2
         10         10

Solução = 1 e 1,2

Espero ter ajudado!  :D